Heat partition evaluation during dry drilling of thick CFRP laminates with polycrystalline diamond drills - Shariar, Fahim; Karaguzel, Umut; Karpat, Yigit (ELSEVIER, 2024)
Since various material properties of carbon fiber-reinforced polymer (CFRP) are temperature dependent, dry drilling of CFRP is a delicate process. Thermal damage can be caused by a rise in temperature during drilling due to a large portion of heat being transferred into the material. Heat partition is used to quantify this, which represents the percentage of total heat being dissipated into the constituent objects during a machining operation. Drill margin and contact conditions at the tool-workpiece interface significantly affect the drilling of CFRP material. Drilling experiments were performed to measure thrust force, torque, and temperatures for five different sets of feed rates and rotational speeds. This study proposes a method for calculating heat partition values during CFRP drilling by developing a finite element-based thermal model. The FE model employs a Gaussian distributed ring-type heat flux that is a function of the equivalent contact length at the interface between the drill and the material surface and the geometry of the workpiece which operates as a moving heat source, emulating the progress of the drill through the CFRP laminate. The tool implements heat fluxes that use characteristic time-point-based step functions to represent the temperature on the drill as it advances through the workpiece during machining. The temperature profiles obtained from the FE analysis and the experiments for the workpiece and tool were subsequently matched iteratively to determine the corresponding heat partition value. (c) 2024 The Authors. Published by ELSEVIER Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)
Keywords: Fiber-reinforced polymer; Drilling; Heat partition; FLOW; Engineering; Materials Science